'Unestablished' biological control agent found in Canterbury 40 years later. Issue 1 (2nd January 2017) - Romo, C. M.; Early, J. W.; Massart, X.
ABSTRACT: The polyphagous ectoparasitoid, Rhopalicus tutela (Walker), introduced to New Zealand as a biological control agent of Hylastes ater (Paykull) during the 1970s, has recently been collected from a forest park in Canterbury. Researchers previously thought that the species had failed to establish at release sites around the North Island. Monitoring of the species was ceased in 1985 and research into its potential to control bark beetle populations was abandoned. Mystery surrounds whether the discovered population is part of the original introduction or may have arrived to New Zealand on its own.